Influencia de las tareas escolares en el desarrollo psicosocial en los niños y niñas de primer año de educación general básica paralelo “b” jornada vespertina de la Unidad Educativa “Vicente León” en el periodo académico 2016-2017 - Iza Salazar, Gabriela Enriqueta (2017)
At present the academic formation of the children is relevant, so that there has been the need of research the influence that the homework has in the psychosocial development of the children, this project reached a wide epistemology both in parents and teachers, who are tightly related in the evolutionary process of the infant. The objective of the investigation was analyzed the effects that homework has to improve the development of the children inside teaching- learning process, which were used as methodological strategies by the teachers to achieve the educational objectives of the school year. The research methodology that was applied is mixed, so that, it allows collecting qualitative and quantitative data to the people related to the research, the homework at home has both positive and negative consequences in the educational and social area, the application of investigative techniques were also performed, like interview, poll and observation with its respective instrument and analysis of the results to know personal opinion of educational actor that it´s related to the children´s developmental, social and academic process….